(untitled) (Research, Society and Development, 2020)
Objectives: to identify the existence of venous thromboembolism (VTE) prevention measures in inpatient units of a public health system university hospital and to apply a clinical record for the screening of VTE risks by nurses. Method: transversal, descriptive and quantitative approach study, carried out in units of a quaternary university hospital of the Public Health System, located in the city of Rio de Janeiro. A total of 43 nurses participated and 90 medical records of hospitalized patients were used. Data collection was performed through two instruments: a form and a "VTE risk and conduct assessment form". The collected data were organized in Excel spreadsheets and for data analysis simple descriptive and analytical statistics were used. Results: It was identified that most nurses do not record prophylactic actions and do not know protocols or algorithms about VTE. The most frequent risk factors in patients were: age over 40 years, prolonged immobility and use of central catheter or Swan-Ganz. Conclusion: the existence of underreporting in the medical charts made by nurses limited or prevented prophylactic actions by the multidisciplinary health team, as well as there were no protocols or algorithms for VTE prevention for use by nurses in the hospitalization units.